2021
DOI: 10.3310/hsdr09100
|View full text |Cite
|
Sign up to set email alerts
|

Identifying determinants of diabetes risk and outcomes for people with severe mental illness: a mixed-methods study

Abstract: Background People with severe mental illness experience poorer health outcomes than the general population. Diabetes contributes significantly to this health gap. Objectives The objectives were to identify the determinants of diabetes and to explore variation in diabetes outcomes for people with severe mental illness. Design Under a social inequalities framew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 180 publications
(152 reference statements)
1
8
0
Order By: Relevance
“…Nevertheless, severity of disease might influence diabetes self management. 12 Overall, this study suggests that diabetes targets can be achieved by people with diagnosed mental illness in an urbanised, socio-economically diverse area. Diabetes monitoring and recognition of mental illness appear to represent the 'protective key' in the association of mental illness with achieving treatment targets.…”
Section: Strengths and Limitationsmentioning
confidence: 73%
See 4 more Smart Citations
“…Nevertheless, severity of disease might influence diabetes self management. 12 Overall, this study suggests that diabetes targets can be achieved by people with diagnosed mental illness in an urbanised, socio-economically diverse area. Diabetes monitoring and recognition of mental illness appear to represent the 'protective key' in the association of mental illness with achieving treatment targets.…”
Section: Strengths and Limitationsmentioning
confidence: 73%
“…A longer duration of mental illness was positively associated with reaching targets, suggesting that disruption due to mental illness can only be improved by recognition and treatment of problems. Previous studies have reported both impaired 6,26,27 and improved 8,12,28 glycaemic control in people with diabetes and depression. Improved HbA 1c and SBP control in adults with mental illness might have been influenced by healthcare and self management, as only care users were included in our study.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations